Dentists Knowledge Regarding Antibiotic Prescription, and Dosage of the Prescribed Antibiotics - Anam Mahmood, Hiba Tabassum, Sarfaraz Hussain, Muzaffar Qayum Khan Ghauri, Fida Baloch, Jawaid Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prescription pattern for antibiotics, which antibiotics were prescribed most frequently, and the dosage of antibiotics prescribed. Methodology: This cross-sectional investigation was performed from May 2014 to July 2014. A total of 100 practicing dentists were selected at random. This study consisted of two portions. In part 1 (prescriptions), dentists were asked to fill out a questionnaire regarding the antibiotics they prescribed over a period of 4 weeks. In part 2 (self-reported practice), dentists were asked to complete a questionnaire regarding their general information, their specialty, and their knowledge about the prescription of antibiotics. Dentists were also asked to mention if their prescription was therapeutic or prophylactic, cases in which antibiotics were prescribed, and also mention the treatment plan. All data was collected and registered on a predesigned Proforma. Results: A total of 100 dentists were interviewed regarding antibiotic prescriptions. Out of all, 37 were females and 63 were males, and their mean age was 33.02 years. The most commonly recommended antibiotic was amoxicillin (49%), followed by amoxicillin + Clavulanic acid (33%). The commonest reason for the prescription of antibiotics was periapical infection (43%), followed by, periodontitis (14%), simple extraction (10%), and (pulpits 9%) and remaining reasons. Out of the all, most of the individuals (82%) had prescribed due to therapeutic reasons and 18 due to prophylactic reasons. Conclusion: It is concluded that the several of the dentists were prescribing antibiotics for several oral conditions where local administration would be adequate and antibiotics were unnecessary. Keywords: Prescription, Antibiotics, Resistance.